(untitled) (Experimental biology, 2016)
At the present time, in Kazakhstan there are trend towards to degradation of pastures. This poses the problem of their restoration. The most promising solutions - using EM technology, based on the introduction in soil of EM-association. The aim this study was selection of strains, creation of EM-associations, study of their effect on meadow grass and biological activity of the soils. From the ecologically pasture’s soil of Almaty region the nitrogen-fixing, cellulolytic and phosphatemobilizing bacteria were isolated. Their biocompatibility was studied, nine strains of were selected. From them 84 variants were created. For the selection perspective EM-associations, their effect on meadow grass and soil biological activity was studied. The inoculation of seed with EM-associations increased green biomass of meadow grasses on the 25-30%. The introduction EM-associations in the soil increased activity of the soil’s enzymes (dehydrogenase increased in 6.2-7.0, catalase and urease in 4.5-5.0 times), and soil respiration in 6-7 times as compared with control. On the basis of these EM-associations will be possible to restoration of the degraded pasture soils.